Maternal anaemia and its severity: an independent risk factor for preterm delivery and adverse neonatal outcome - Rani, Kumari Usha; Gupta, Jyoti; Gupta, Ratan; Aggarwal, Kailash Chander (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was done to evaluate the effect of maternal anaemia and its severity on gestational age and neonatal outcome. Methods: This was a retrospective study, conducted in Vardhman Mahavir medical college and Safdarjang hospital, New Delhi between April 2012 to March 2013. Cases were divided in three groups i.e. non anaemic, mild to moderately anaemic and severely anaemic (according to WHO classification). A total of 1050 woman (350 in each group) were recruited for study. The following outcome measures were used: preterm delivery (<37 weeks), birth weight, APGAR score, admission of baby in neonatal intensive care unit and early neonatal death. Data was analyzed by Chi-square test. A P value of or less than 0.05 was considered as significant. Results: The risk of preterm delivery, low birth weight, poor APGAR score and admission of baby in neonatal intensive care unit was more in anaemic group and it increased with severity of anaemia which was statistically significant. The increase in risk of early neonatal death was not significant in mild/moderate anaemic group (P value 0.326) while it was statistically significant in severely anaemic group (P value 0.004). Conclusions: Anaemia in pregnancy has a recognizable association with prematurity, low birth weight and poor neonatal outcome.